The effect of supplementation by different nitrogen sources on the production of bioethanol from sago hampas by saccharomyces cerevisiae - Siti Hajar, Binti Yacob (University Malaysia Sarawak, UNIMAS., 2013)
As the world getting exhausted with the fuels utilization based on petroleum, there is high demand for bioethanol as alternative to fossil fuels. Nowadays, the production of bioethanol from agricultural wastes is the one of the sources that commonly used. In this study, the Sago hampas was used act as carbon sources (substrate) for bioethanol production. Instead a carbon source, the nitrogen sources also is one of the crucial components required in the production of bioethanol. In this study, urea is the most suitable nitrogen source to be supplemented with Sago Hampas Hydrolysate (SHH) because the higher production ethanol have been obtained, 8.639 g/L within 8 hours of fermentation at 16.169 g/l of initial glucose concentration.. In addition, urea is an inexpensive nitrogen source and also economically attractive for the industrial production of fuel alcohol. The production of bioethanol of sago hampas have been carried out by submerged batch fermentation process by S.cerevisiae at pH 5.5-5.6, temperature of 30ºC in 100 ml working volume. From this study, instead yeast extract that commonly used in study, other type of nitrogen sources such as urea or ammonium ion also have been used in order to produce higher production of bioethanol by S. cerevisiae from SHH.